A Study of Post COVID-19 Disaster in Indonesia: A Lesson Learned is a Lesson Earned - Khairatun Hisan, Urfa; Miftahul Amri, Muhammad; Afira Pramesti, Tarisa; Rahmawati, Indah (Ahmad Dahlan Medical Journal, 2022)
The rapid and sudden arrival of the COVID-19 pandemic has overwhelmed everyone. In this article, the author summarizes various issues and problems in Indonesia that arose during the COVID-19 pandemic. These issues included the desecuritization of the COVID-19 issue; the masks scarcity and high price of masks; public confusion over the policy of testing, tracing, treatment (3T), social restriction policies, and terms related to COVID-19 that often change; social problems and poverty; rumors and fake news that accompany vaccination program; shortage of medical equipment and health resources; and the problems experienced by medical personnel such as fatigue, mental health issues, and even death. It is known that COVID-19 is a new virus. Therefore, at the pandemic’s beginning, no one knew its characteristics and how to deal with it. This confuses policy makers around the world in formulating a formula to deal with COVID-19. Subsequently, the policies often change according to the development of the virus and science itself. Thanks to the stakeholders’ role, the pandemic situation in Indonesia has gradually recovered. However, there are some notes that we can learn from Indonesia’s pandemic to avoid the same problem if similar conditions occur in the future. As the title of this paper, "a lesson learned is a lesson earned". Finally, the authors summarize four formulas to minimize similar problems in the future, including: 1) strengthening medical resources and infrastructures; 2) disease prevention through health promotion and education; 3) strengthening the national emergency institutions; and 4) improving crime and corruption surveillance system.